Prognostic value of pseudotime from texture parameters of FDG PET/CT in locally advanced rectal cancer with neoadjuvant concurrent chemoradiotherapy - Lee, Hyunjong; Hyun, Seung Hyup; Cho, Yong Beom; Kim, Hee Cheol; Park, Hee Chul; Park, Young Suk; Choi, Joon Young (Scientific reports, 2024)
Texture analysis generates image parameters from F-18 fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT). Although some parameters correlate with tumor biology and clinical attributes, their types and implications can be complex. To overcome this limitation, pseudotime analysis was applied to texture parameters to estimate changes in individual sample characteristics, and the prognostic significance of the estimated pseudotime of primary tumors was evaluated. Our subjects were 224 rectal cancer patients who underwent pretherapeutic FDG PET/CT and neoadjuvant concurrent chemoradiation therapy (CCRT). Texture parameters of the primary tumor were extracted from FDG PET/CT images acquired before neoadjuvant CCRT. The pseudotime of the primary tumor was successfully derived from texture parameters using the Phenopath tool. Clinico-pathologic features were obtained and survival analysis was performed. Pseudotime, metabolic tumor volume (MTV), and total lesion glycolysis (TLG) demonstrated significant associations with overall survival. Unlike MTV and TLG, pseudotime was an independent prognostic factor for overall survival (hazard ratio = 4.807, p-value = 0.037). Pseudotime analysis integrates various metabolic texture parameters into a single metric. Pseudotime estimated from FDG PET/CT images of primary tumors shows superior prognostic significance to conventional PET parameters in patients with locally advanced rectal cancer treated with tri-modality therapy.